Characteristics and prognosis of patients with mild cognitive impairment by cerebrospinal fluid biomarker profiles: Biomarkers (non‐neuroimaging)/Prognostic utility. (7th December 2020) - Estellés, Teresa; Carmona‐Iragui, Maria; Illán‐Gala, Ignacio; Barroeta, Isabel; Sánchez‐Saudinós, Maria Belen; Sala, Isabel; Morenas‐Rodríguez, Estrella; Altuna, Miren; Santos‐Santos, Miguel A; Xucla, Tomás; Blesa, Rafael; Fortea, Juan; et al.
Abstract: Background: Biomarkers have an important diagnostic and prognostic value in neurodegenerative diseases, especially in early stages. We analyzed the differences in baseline characteristics and clinical evolution of patients with mild cognitive impairment (MCI) according to their cerebrospinal fluid (CSF) Alzheimer Disease biomarkers profile. Method: We retrospectively selected all patients evaluated in the Sant Pau Memory Unit that had a neuropsychological evaluation compatible with MCI, analysis of Alzheimer CSF biomarkers and clinical follow‐up for at least 6 months. Patients were classified applying our internal cutoffs for CSF levels of Aβ1‐42 as a marker of amyloidosis (A+/A‐) and CSF levels of pTau as a marker of Tau pathology (T+/T‐).We compared demographic characteristics, cognitive progression, and final clinical diagnoses between groups. Result: We included 274 participants: 103 A‐/T‐, 43 A+/T‐, 40 A‐/T+ and 88 A+/T+. The mean follow‐up was 3.4 years. Patients in the A‐/T‐ group were younger (67.8 years) compared to those in the A+/T+ group (72.3 years, p=0.002). During follow‐up, the A+/T+ group showed greater global cognitive impairment (‐1.5 MMSE score/year; p <0.001)and higher risk of progression to dementia (OR=3, 13, p<0.001). There were no differences in baseline neuropsychological scores between A+/T‐ and A‐/T+ groups. The proportions of patients with a final clinical diagnosis of Alzheimer's dementia (AD), Lewy body Dementia (LBD) and frontotemporal lobar degeneration related syndromes(FTLD) were 37%, 16% and 12% in the A+/T‐ group, and 25%, 10% and 5% in the A‐/T+ group, respectively. Compared to the A+/T‐ group, the A‐/T+ group had a higher proportion of patients whose final clinical diagnosis was non‐neurodegenerative or undetermined (60% vs. 35%, respectively; p=0.022) and a lower risk of progression to dementia (OR=0.37; p=0.032). Conclusion: A CSF profile suggestive of AD pathophysiology is associated with greater global cognitive impairment and a higher risk of progression to dementia. Although we did not find differences in baseline neuropsychological scores between patients with positive markers of amyloidosis and those with tau pathology only, patients with amyloidosis showed a higher risk of progression to dementia in follow‐up. The benefit of using additional markers of amyloidosis and/or tau pathology in the assessment of prognosis of these patients needs to be further explored.